The Utilization of AI-Based Chatbots as Interactive Learning Media to Enhance Students’ Understanding of Islamic Cultural History - Euis Naini Bintara Wardani; Ikhwan Aziz Q; Adi Wijaya (CV. Creative Tugu Pena, 2025)
The low level of students’ interest and engagement in learning Islamic Cultural History (Sejarah Kebudayaan Islam or SKI) remains a persistent issue, primarily due to the use of less varied teaching methods, despite the availability of technological facilities in madrasahs. This condition highlights the need for innovative learning media that align with the characteristics of learners in the digital era. This study aims to examine the use of Artificial Intelligence based chatbots as interactive learning media to enhance students’ understanding of SKI and to explore students’ learning experiences and perceptions of their use. The research employed a qualitative approach using a case study method conducted at MTs Manbaul Ulum Seputih Surabaya. Research participants were selected through purposive sampling and included SKI teachers, AI and Coding teachers, and the head of a ninth grade class. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that AI based chatbots function as supportive learning media that enhance interactivity, help students understand learning materials more concisely, and encourage active participation in the learning process. However, their use is not optimal without proper guidance and teacher facilitation. These findings emphasize the importance of pedagogically integrating AI based chatbots into SKI learning to improve students’ understanding while maintaining the internalization of Islamic values.